1992
DOI: 10.1002/j.1460-2075.1992.tb05598.x
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage colony stimulating factor activates phosphatidylcholine hydrolysis by cytoplasmic phospholipase A2.

Abstract: The macrophage colony stimulating factor (M‐CSF) is required for the proliferation and differentiation of monocytes. Previous studies have demonstrated that M‐CSF stimulation is associated with phosphatidylcholine (PC) hydrolysis and increased formation of both diacylglycerol (DAG) and phosphorylcholine. The present work extends those results by demonstrating that treatment of human monocytes with M‐CSF is associated with increases in a cytoplasmic Ca(2+)‐dependent activity which hydrolyzes 1‐palmitoyl,2‐arach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
1

Year Published

1993
1993
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(66 citation statements)
references
References 51 publications
3
62
1
Order By: Relevance
“…Another possibility is that lyso-PC may enter cells and serve as an intracellular second messenger with JNK as a downstream target. This hypothesis has been strengthened by a series of studies demonstrating that lyso-PC was generated intracellularly through activation of phospholipase A 2 following stimulation of tyrosine kinase receptors by macrophage colony-stimulating factor (23), and stimulation of G-proteincoupled receptors by thrombin (24,25), bombesin (26), interferon-␥ (27), or angiotensin (28,29). The identification of potential intracellular effectors of lyso-PC should help in elucidating the mechanism(s) for the multiple biological functions of this phospholipid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is that lyso-PC may enter cells and serve as an intracellular second messenger with JNK as a downstream target. This hypothesis has been strengthened by a series of studies demonstrating that lyso-PC was generated intracellularly through activation of phospholipase A 2 following stimulation of tyrosine kinase receptors by macrophage colony-stimulating factor (23), and stimulation of G-proteincoupled receptors by thrombin (24,25), bombesin (26), interferon-␥ (27), or angiotensin (28,29). The identification of potential intracellular effectors of lyso-PC should help in elucidating the mechanism(s) for the multiple biological functions of this phospholipid.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that lyso-PC significantly potentiated protein kinase C (PKC)-mediated cellular responses such as primary T-lymphocyte activation (20,21) and HL-60 cell differentiation into macrophages (22). Since actions of many extracellular agonists are associated with the activation of membrane phospholipase A 2 and the subsequent accumulation of lyso-PC (23)(24)(25)(26)(27)(28)(29), it is conceivable that lyso-PC may act as a second messenger, transducing signals elicited from membrane receptors. This is consistent with experiments showing that lyso-PC and phospholipase A 2 under certain circumstances have similar effects when incubated with cultured cells (21,22).…”
mentioning
confidence: 99%
“…sion was also documented in certain cytokine-treated cells (Schalkwijk et al, 1992, Nakamura et al, 1992Lin et al, 1992b). It was reported previously that cPLA, prepared from the mouse macrophage-like cell line, RAW264.7, apparently exhibited both phospholipase A, and lysophospholipase activities (Leslie, 1991), although the activity of phospholipase A, was about 10% that of phospholipase A,.…”
mentioning
confidence: 88%
“…Phosphorylation of cPLA 2 in Human Monocytes-cPLA 2 plays a key role in releasing arachidonic acid for prostaglandin production in human monocytes, and previous studies revealed that monocyte cPLA 2 is regulated by phosphorylation (2,38). Therefore, monocytes were used to determine if similar sites were phosphorylated on cPLA 2 in a mammalian system, as identified on the cPLA 2 expressed in Sf9 cells.…”
Section: Stimulated Arachidonic Acid Release By Sf9 Cells Expressing mentioning
confidence: 99%